Weakly Nonlinear Fredholm Integral Equations with Degenerate Kernel in Banach Spaces - Zhuravlyov V. Р. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We consider weakly nonlinear Fredholm integral equations with degenerate kernel in Banach spaces and establish a necessary condition and sufficient conditions for the existence of solutions of equations of this kind. The convergent iterative procedures are proposed for the construction either of a single solution or of at least one possible solution.